2015
DOI: 10.4238/2015.january.15.2
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis of ultrasonic characteristics, pathological type, and molecular markers of thyroid nodules

et al.

Abstract: ABSTRACT. The present study was conducted to analyze the correlation between ultrasonic characteristics, pathological type, and molecular markers of thyroid-tumor-related genes as well as to evaluate the diagnosis and prognosis of thyroid nodules. The acoustic characteristics of 130 thyroid specimens were detected. Pathological sectioning and immunohistochemical detection were performed to determine the correlation between tumor gene expression and ultrasonic characteristics. Ultrasonic testing revealed that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Ki67 frequently exhibits increased expression in patients with anaplastic carcinoma and malignant nodule tumors (22,23). In the present study, it was observed that SERPINE2 knockdown reduced Ki67 and PCNA expression levels.…”
Section: Discussionsupporting
confidence: 61%
“…Ki67 frequently exhibits increased expression in patients with anaplastic carcinoma and malignant nodule tumors (22,23). In the present study, it was observed that SERPINE2 knockdown reduced Ki67 and PCNA expression levels.…”
Section: Discussionsupporting
confidence: 61%
“…In our study, we analyzed the classification of benign and malignant nodules using measures of thyroid function. Changes in FT4, FT3, TSH, and TG are common indicators of changes in thyroid function (12)(13)(14)(15). These indicators were analyzed and modeled; both FT4 and FT3 had significant effects on malignant nodules and were key factors that could be used to diagnose benign and malignant nodules.…”
Section: Association Between Thyroid Function Tests and Nodule Classi...mentioning
confidence: 99%
“…Thyroid cancer (TC) is a malignant tumor derived from thyroid epithelial cells, and the increased incidence of TC is a serious concern. 1,2 At present, the specific molecular mechanism of TC has not been reported. Like other malignancies, the external environmental and intracorporal genetic are known to be important factors influencing the pathogenesis of TC.…”
Section: Introductionmentioning
confidence: 98%